Carnosol Modulates Th17 Cell Differentiation and Microglial Switch in Experimental Autoimmune Encephalomyelitis - Li, Xing; Zhao, Li; Han, Juan-Juan; Zhang, Fei; Liu, Shuai; Zhu, Lin; Wang, Zhe-Zhi; Zhang, Guang-Xian; Zhang, Yuan (Frontiers in Immunology, 2018)
Small natural molecules derived from medicinal plants have long been considered as a rich pool of novel therapeutic medicine. Carnosol is a bioactive diterpene compound derived from Rosmarinus officinalis (Rosemary) and Salvia officinalis, herbs widely used in traditional medicine for the treatment of various inﬂammatory diseases. In this study, we investigated the eﬀects and mechanism of action of carnosol in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). Carnosol treatment eﬀectively ameliorated clinical disease severity in the myelin oligodendrocyte glycoprotein (MOG) 35–55 peptide-induced EAE model, significantly decreased inflammatory cell infiltration into the CNS and reduced demyelination. Further, carnosol inhibited Th17 cell diﬀerentiation and STAT3 phosphorylation, and blocked transcription factor NF-κB nuclear translocation. In the passive-EAE model, carnosol treatment also significantly prevented Th17 cell pathogenicity. Moreover, carnosol exerted its therapeutic effects in the chronic stage of EAE, and, remarkably, switched the phenotypes of infiltrated macrophage/microglia. Taken together, our findings demonstrate that carnosol has significant potential as a therapeutic agent for autoimmune diseases such as MS.